Hypochlorous Acid: From Innate Immune Factor and Environmental Toxicant to Chemopreventive Agent Targeting Solar UV-Induced Skin Cancer - Snell, Jeremy A.; Jandova, Jana; Wondrak, Georg T. (Frontiers in Oncology, 2022)
A multitude of extrinsic environmental factors (referred to in their entirety as the ‘skin exposome’) impact structure and function of skin and its corresponding cellular components. The complex (i.e. additive, antagonistic, or synergistic) interactions between multiple extrinsic (exposome) and intrinsic (biological) factors are important determinants of skin health outcomes. Here, we review the role of hypochlorous acid (HOCl) as an emerging component of the skin exposome serving molecular functions as an innate immune factor, environmental toxicant, and topical chemopreventive agent targeting solar UV-induced skin cancer. HOCl [and its corresponding anion (OCl-; hypochlorite)], a weak halogen-based acid and powerful oxidant, serves two seemingly unrelated molecular roles: (i) as an innate immune factor [acting as a myeloperoxidase (MPO)-derived microbicidal factor] and (ii) as a chemical disinfectant used in freshwater processing on a global scale, both in the context of drinking water safety and recreational freshwater use. Physicochemical properties (including redox potential and photon absorptivity) determine chemical reactivity of HOCl towards select biochemical targets [i.e. proteins (e.g. IKK, GRP78, HSA, Keap1/NRF2), lipids, and nucleic acids], essential to its role in innate immunity, antimicrobial disinfection, and therapeutic anti-inflammatory use. Recent studies have explored the interaction between solar UV and HOCl-related environmental co-exposures identifying a heretofore unrecognized photo-chemopreventive activity of topical HOCl and chlorination stress that blocks tumorigenic inflammatory progression in UV-induced high-risk SKH-1 mouse skin, a finding with potential implications for the prevention of human nonmelanoma skin photocarcinogenesis.